The secreted host-cell protein clusterin interacts with PmpD and promotes Chlamydia trachomatis infection - Fabienne Kocher; Johannes H. Hegemann (Frontiers in Cellular and Infection Microbiology)
Attachment and uptake into host cells are pivotal steps in the life cycle of the Chlamydiaceae, a family of obligate intracellular pathogens. Chlamydia trachomatis (Ctr) possesses a family of nine polymorphic membrane proteins (Pmps), which have been shown to be crucial for adhesion and internalization. However, the host-cell molecules involved have so far remained unknown. Here, we show that a fragment of Ctr PmpD, which forms high-molecular-weight oligomers in solution and adheres to epithelial cells, also binds to secreted clusterin (sCLU), a chaperone-like protein that is secreted into the extracellular space by the host cell, and forms part of the chaperone- and receptor-mediated extracellular protein degradation (CRED) pathway. Using in vitro assays, we demonstrate that sCLU interacts directly with soluble rPmpD. In infection experiments, depletion of sCLU from the culture medium leads to a significant decrease in Ctr infection. Thus, sCLU is the first host-cell interaction partner identified for a Ctr Pmp and the first case in which sCLU has been shown to be a vital component for the establishment of a bacterial infection.